Health-related quality of life in patients treated with pembrolizumab for microsatellite instability–high/mismatch repair–deficient advanced solid tumours: Results from the KEYNOTE-158 study. (July 2022) - Maio, Michele; Amonkar, Mayur M.; Norquist, Josephine M.; Ascierto, Paolo A.; Manzyuk, Ludmila; Motola-Kuba, Daniel; Penel, Nicolas; Cassier, Philippe A.; Bariani, Giovanni M.; De Jesus Acosta, Ana; Doi, Toshihiko; Longo, Federico; et al.
Abstract: Background: In the KEYNOTE-158 study (NCT02628067), pembrolizumab showed a high objective response rate and durable clinical benefit for patients with previously treated, unresectable/metastatic microsatellite instability−high (MSI-H)/mismatch repair‒deficient (dMMR) non-colorectal solid tumours. We present health-related quality of life (HRQoL) results from the MSI-H/dMMR population (cohort K). Patients and methods: Eligible patients had previously treated MSI-H/dMMR advanced non-colorectal solid tumours, measurable disease per RECIST v1.1, and ECOG performance status ≤1. Patients received pembrolizumab 200 mg Q3W for 35 cycles (2 years). The EORTC Quality of Life Questionnaire (QLQ-C30) and EQ-5D-3L were administered at baseline, at regular intervals throughout treatment, and 30 days after treatment discontinuation. Prespecified analyses (exploratory endpoints) included the magnitude of change from baseline to post-baseline timepoints in all patients and by the best overall response for QLQ-C30 global health status (GHS)/QoL, QLQ-C30 functional/symptom scales/items, and EQ-5D-3L visual analogue scale (VAS) score. Results: At data cutoff (October 5, 2020), 351 patients were enrolled, of whom 311 and 315 completed baseline QLQ-C30 and EQ-5D-3L questionnaires, respectively. QLQ-C30 GHS/QoL scores improved from baseline to week 9 (mean [95% CI] change, 3.07 [0.19–5.94]), then remained stable or improved by week 111, with greater improvements observed in patients with a best response of complete response (CR) or partial response (PR) (10.85 [6.36–15.35]). Patients with CR/PR showed improvements in physical (5.58 [1.91–9.25]), role (9.88 [3.80–15.97]), emotional (5.62 [1.56–9.68]), and social (8.33 [2.70–13.97]) functioning, and stable cognitive functioning (1.74 [−1.45 to 4.94]). Conclusions: Pembrolizumab generally improved or preserved HRQoL in patients with previously treated MSI-H/dMMR advanced non-colorectal solid tumours. Highlights: Patients with previously treated MSI-H/dMMR cancer received pembrolizumab treatment. Treatment was associated with improved QLQ-C30 GHS/QoL from baseline to week 9. Improvements were greatest among patients with a complete or partial response. Pembrolizumab improved or preserved QoL in previously treated MSI-H/dMMR cancer.